Bullying di Kalangan Siswa dan Pencegahannya Melalui Konseling Islam - Putra, Ahmad; Satriyadi, Budi (Department of Islamic Guidance and Counseling, 2023)
Bullying is no longer something new and taboo, but it has become a worrying threat from ancient times until today. At the end of 2023, the issue of bullying will once again make a dark history in educational institutions in Indonesia, especially schools. Thus, the author considers it important to discuss and study it again as a guide for the general public so that all parties work together to provide protection and security for students wherever they are. The aim of this research is to see how Islamic counseling views respond to the phenomenon of bullying itself and what breakthroughs can be made to prevent bullying from happening again in educational institutions. The method used in this research is library research, where the author strengthens data, explanations, through books, scientific articles and other sources that are considered important and support this paper. The results of this research found that Islamic counseling makes an important contribution in changing human behavior to a more valuable path and expects each individual to build two relationships, namely a good relationship with Allah and with fellow humans. With this provision, humans will live in harmony and build brotherhood with each other.